The effect of starvation on phosphodiesterase activity and the content of adenosine 3′:5′-cyclic monophosphate in isolated mouse pancreatic islets - Capito, Kirsten (1974)
1. The concentration of cyclic AMP and the activity of phosphodiesterase were measured in isolated pancreatic islets from fed or 48h-starved mice. 2. Two different phosphodiesterases were detected. Neither the maximum activity nor the K(m) values of these enzymes were changed by starvation. 3. The concentration of cyclic AMP in non-incubated islets was the same in islets from fed and starved mice. 4. Incubation with 3.3mm-glucose for 5–30min had no effect on the concentration of cyclic AMP, irrespective of the nutritional state of the mice. Incubation with 16.7mm-glucose for 5–30min raised the concentration of cyclic AMP by about 30% in islets from fed mice. This rise was prevented by addition of mannoheptulose (3mg/ml). Incubation with 16.7mm-glucose had no effect on the cyclic AMP content in islets from starved mice. 5. In islets from fed mice 10min incubation with 5mm-caffeine had no effect on the concentration of cyclic AMP in the presence of 3.3 or 16.7mm-glucose, whereas the cyclic AMP content was increased approx. 150% in islets from starved mice. 6. After 10min incubation with 1mm-3-isobutyl-1-methylxanthine in the presence of 3.3 or 16.7mm-glucose the concentration of cyclic AMP was raised by 250% in islets from fed mice and by 400% in islets from starved mice. 7. A threefold function of glucose in the insulin-secretory process is suggested, according to which the decreased islet glucose metabolism is the primary defect in the insulin-secretory mechanism during starvation.